Dieci anni di seconde generazioni in Italia - Flavio A. Ceravolo; Stefano Molina (Quaderni di Sociologia, 2013)
From the end of the twentieth century, Italy has become a destination for international migration. The study of social paths of the children of foreign immigrants has undergone a great development in Italian scientific debate during the last ten years. It has proved to be a relevant theme both from a scientific and a social point of view, forcing scholars to rethink the interpretative paradigms and the theoretical models conventionally used in migration studies. With this article, we aim to evaluate the present situation in the light of the main questions which enhanced the debate ten years ago: which are the main tendencies of the demographic profile of second generations? How has the debate on juridical and effective citizenship of immigrant children? Which is their social image? Have the risks of a subordinate integration been prevented? To answer these questions, we have drawn a synthetic outline of the main essays produced during the last ten years and completed them with critical considerations and further hints for new analytical frameworks.